(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The hoard, found below a deposit of peat included a lead weight, pins of silver, a silver strap end, a gold finger ring and twelve coins. Two hut circles and the fallen walls of a small rectangular dwelling are located nearby.